The Effect of Three Good Things Technique on Self-Leadership to Nursing Students - Diwa Agus Sudrajat; Andalis Munawaroh Aisyah; Suci Noor Hayati; Tria Firza Kumala (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Background: Every nursing student must develop self-leadership skills. It has been proven that nursing students who score high in self-leadership would have better performance and self-efficacy. The Three Good Things intervention is a potential strategy for enhancing self-leadership. Aim: The aimed of the research was to identify the effect of the three nice things technique on nursing students' self-leadership. Method: This research is a quantitative study using a Quasi-Experimental design with Two Group Pre and Post-test, involving 60 nursing students as respondents. Data collection with the RSLQ questionnaire (Revised Self-Leadership Questionnaire) and data analysis using Paired Sample ANCOVA and T-Test Results: This study showed the picture of low self-leadership before intervention both in the control and intervention groups. Then after the intervention, the self-leadership was still low in the control group, while the intervention group showed a high self-leadership, then there was a significant difference in self-leadership between before and after the intervention in the intervention group with a p-value of 0.000 (p<0.05). There was no significant difference between the control before and after the intervention with a p-value of 0.335 (p>0.05). And the three good things intervention proved to have an effect on self-leadership in nursing students (p-value of 0.000). Conclusion: This study showed an effect of providing three good things interventions on self-leadership in nursing students. This research is expected for the institution to conduct training or workshops on self-leadership in maintaining the consistency of student self-leadership in the institution.